An Econometric Analysis of IBRD Creditworthiness - McKenzie, David (World Bank, Washington, D.C., 2013)
The author econometrically ascertains the determinants of default to the International Bank for Reconstruction and Development (IBRD) through panel logit analysis. Creditworthiness with a lag of one period is determined by the extent of arrears to private creditors, the proportion of total debt service that is being paid, the government budget deficit, the extent of military involvement in the government of a country, and by the G7's current account balance. Default to the IBRD falls into a graduated hierarchy, whereby default occurs first to Paris Club and commercial bank creditors, with subsequent default triggered by portfolios with high proportions of IBRD and short-term debt, as well as the factors mentioned above. Default to these other creditor groups can be explained by more traditional country risk variables, although Mckenzie's analysis highlights the importance of political and external factors in explaining default to all creditors studied. He finds sovereign default to be a state-dependent process, whereby the repayment behavior of a country changes once it enters into default. Operationally, the author arrives at a model that can be used to assess short-term creditworthiness, although data imperfections and availability still limit the usefulness of the model for some countries. Longer-term risk assessment proves more difficult, which raises operational questions for the IBRD.